INCREASED LDLP SENSITIVITY TO OXIDATION AS A RISK FACTOR FOR ATHEROSCLEROSIS - Y. P. Nikitin; Y. I. Ragino (Российский кардиологический журнал, 2002)
Increased LDLP sensitivity to oxidation as a risk factor for atherosclerosis.